Association between brachial‐ankle pulse wave velocity and cardiovascular and cerebrovascular disease in different age groups. Issue 3 (23rd January 2022) - Sang, Da Sen; Zhang, Qi; Song, Da; Tao, Jie; Wu, Shou Ling; Li, Yong Jun
Abstract: Background: To investigate the association between brachial‐ankle pulse wave velocity (baPWV) and cardiovascular and cerebrovascular disease (CVD) in different age groups. Methods: A total of 39 417 people, receiving Kailuan physical examination, completing baPWV examination from 2010 to 2017, with no history of CVD and atrial fibrillation, were selected as the observation objects. The population was categorized into one age group per 10 years, namely the <50, 50–59, 60–69, 70–79, and ≥80‐year‐old groups, and the total population, and each group was further assigned into three classes according to the triple quartiles of baPWV. Kaplan–Meier method helped to calculate the cumulative incidence of CVD in different age groups. The effect of baPWV on CVD in different age groups was evaluated using the Cox proportional hazards regression model. Results: Kaplan–Meier survival curve indicated statistical significance ( p < .05) in the cumulative incidence of CVD among the whole population, <50, 50–59, and 60–69‐year‐old groups, while the cumulative incidence of end‐point events among the baPWV subgroups of 70–79 and ≥80‐year‐old groups exhibited no statistical significance ( p > .05). Compared with baPWV in the Q1 group, hazard ratio value (95% confidence interval [CI]) of CVD in the Q3 group was 4.14 (95% CI: 2.98–5.75) in the total population, 2.98 (95% CI: 1.08–8.21) in <50‐year‐old population, 4.49 (95% CI: 2.89–7.00) in 50–59‐year‐old population, 2.78 (95% CI: 1.76–4.39) in 60–69‐year‐old population, 1.39 (95% CI: 0.86–2.24) in 70–79‐year‐old population, and 1.15 (95% CI: 0.55–2.41) in ≥80‐year‐old population. Conclusion: CVD risk attributed to increased arterial stiffness reduces with age.